PENGARUH BEBAN KERJA, STRES KERJA, MELALUI KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA UNIT PELINDUNGAN BP2MI - Usman Bestari, (2021)
The theme of the performance of the State Civil Apparatus (ASN) is still a public concern, especially in encouraging government organizations to improve performance so that some research related to the performance of ASN employees is common. Problems that are often encountered in the work environment are fluctuations in employee job satisfaction acceptance, whether or not work stress and workload distribution. Including the Protection unit at BP2MI which intersects the characteristics of the work that facilitates the handling of PMI problems. On the occasion in this study has the purpose and purpose to: 1) know the influence of workload on employee job satisfaction; 2) know the influence of work stress on employee job satisfaction;3) know the influence of workload on employee performance;4) know the effect of work stress on employee performance;5) know the effect of job satisfaction on employee performance in bp2MI protection unit. The subject of this study was an officer who worked on handling pmi protection. The samples in this study amounted to 79 employee. Sampling uses saturated sampling. The collection of research data was conducted using e-kueisoner, where e-kueisoner employee performance (12 items valid), e-kuesioner work satisfaction (14 items valid), e-kuesioner workload (6 items valid), and e-kuesioner work stress (6 items valid). The analysis techniques used on this occasion are path analysis and hypothesis testing using partial testing (t-test), and determination coefficients using Statistical Package for the Social Sciences (SPSS) version 20. The results of the data analysis show that: (1) workload affects employee job satisfaction. (2) Work stress will affect employee job satisfaction. (3) Workload has an impact on employee performance. (4) Work stress will affect performance. (5) Job satisfaction has an impact on performance.